A descriptive study of patients presenting with a chief complaint of seizures to the prehospital emergency care practitioner of the Western Cape - Bester, Beatrix Hendrina (Department of Surgery, 2020)
Background Seizures are considered one of the most common time-sensitive and potentially life-threatening medical emergencies presenting to emergency centres and attended to by prehospital emergency care practitioners. These require a rapid response, prompt identification and appropriate management. There is a paucity of information describing the demographics and prehospital management of patients presenting with seizures in South Africa. Objectives The aim of this study was to describe the demographics and prehospital management of patients presenting with a chief complaint of seizures and/or convulsions to prehospital emergency care practitioners within the Western Cape Government Emergency Medical Services. Methods This retrospective study included all Western Cape Government Emergency Medical Services calls indicating a chief complaint of seizures and/or convulsions between August 2017 and July 2018. Descriptive statistics were performed to describe basic demographics in this population. A sample of emergency calls originating within the City of Cape Town was selected for a clinical chart review to describe on-scene clinical presentation and vitals, response times, and prehospital treatment provided. Results A total of 24 746 seizure and/or convulsion cases were recorded during the study period. The highest frequency of patients was in the 21 - 40 year age group (31%), and 57% of patients were male. The subsample (n=3 075) yielded 1 571 cases with completed electronic patient care records. The mean dispatch and response times were 20 (±36) and 14 (±10) minutes respectively with a mean on-scene time of 25 (±13) minutes. No on-scene vital signs were recorded in 11.3% of patients. Recorded on-scene vitals indicated that 36% of patients presented with a tachycardia, 14% had an oxygen saturation of < 95%. Airway manoeuvres were performed in 30% of cases, and 50% of patients presenting with a SpO2 < 95% received supplemental oxygen. The benzodiazepine Diazepam was the most common medication administered, and 83% of medications were administer through the intravenous route. Conclusions Seizures are a recognised time-sensitive emergency, however in this sample of patients we observed a longer than expected dispatch time. Although the importance of recording baseline vital signs is recognised, there was a large proportion of undocumented vital signs 35 within the sample. Despite consensus recommendations that intramuscular midazolam are the preferred medication and route, IV diazepam was the most frequently administered. Seizures are an under-recognised burden on Emergency Medical Services within the Western Cape. This study provides an initial description of the epidemiology within this population, allowing for optimization of recognition and management in these patients.